External Economies at the Firm Level: Evidence from Swedish Manufacturing - Tomas Lindström (Sveriges Riksbank, 1999)
Using the method of Caballero and Lyons (1990, 1992), I examine detailed Swedish manufacturing firm-level data on output and factor inputs from 1979 through 1994. Panel regressions show that an increase in aggregate output and inputs appears to raise individual firms production beyond private marginal returns, a result consistent with external economies. However, while considering potential specification difficulties, this paper shows that a model in which random shifts in technology drive the business cycle statistically outperforms the Caballero-Lyons model. This finding suggests that high-frequency random shifts in technology are more important for movements in firms productivity than are external economies.
Keywords: D24; L60; 330; business fluctuations; economic growth; increasing returns; manufacturing